Ileo‐rectal anastomosis in ulcerative colitis—Long‐term outcome, failure and risk of cancer at a tertiary centre. (11th July 2022) - Berghog, John; Hermanson, Maria; de la Croix, Hanna; Bengtson, Jonas; Block, Mattias
Abstract: Aim: Ileo‐rectal anastomosis (IRA) is an option to restore bowel continuity after colectomy in patients with ulcerative colitis (UC). Concerns that the remaining rectum may serve as a site for continuing proctitis with subsequent poor function and IRA failure and the fear of development of dysplasia and cancer have led to the abandonment of IRA in large parts of the world. This study investigated the outcome of IRA in a large patient cohort with UC and IRA with regard to failure of IRA and development of dysplasia and cancer. Methods: This was a retrospective data gathering of patients with UC and IRA enrolled at the Department of Colorectal Surgery, Surgical Clinic, Sahlgrenska University Hospital/Östra, Gothenburg, 1972–2019. End‐points were IRA failure, rectal dysplasia and cancer. IRA survival analysis and the cumulative probability of rectal cancer were calculated. Results: In total, 183 patients (121 men) were included in the study. The IRA failure rate was 34% and the estimated cumulative IRA failure rates were 25% and 35% at 5 and 10 years respectively. Four patients developed rectal cancer and the estimated cumulative probability of rectal cancer was 3% and 6% at 10 and 15 years respectively. Conclusion: Ileo‐rectal anastomosis remains a restorative option after colectomy for UC, even if the failure rate raises some concern. Further knowledge is needed for optimal patient selection to avoid early IRA failures. With increasing probability of rectal cancer over time a vigilant surveillance protocol is mandatory.